Las masas de agua del océano pacifico tropical frente a Costa Rica (ING) - Brenes., Carlos L. (1984)
The main water masses in the Tropical Pacific Ocean in front of Costa Rica have been studied.  The subsurface water masses were analized using the Core Layer Method. The matter masses found in this area were: 1. The Tropical Surface Water, 2. The subtropical Subsurface Water, characterized by a high salinity core valve graeter than 34,9%  and 3. The Antarctic Intermediate Water, characterized by a salinity minimum close to 34, 55%